Risk factors for progression of chronic kidney disease in the EPPIC trials and the effect of AST-120 - Schulman, Gerald; Ritz, Eberhard (Clinical and experimental nephrology, 2017)
Background: Two randomized, double-blind, placebo-controlled trials (EPPIC-1 and EPPIC-2) investigated the efficacy and safety of AST-120, an oral spherical carbon adsorbent, in adults with chronic kidney disease (CKD). While the benefit of adding AST-120 to standard therapy was not supported by these trials, we performed a post hoc analysis to focus on CKD progression and to determine the risk factors for the primary endpoint in the EPPIC trial population. Methods: In the EPPIC trials, patients were randomly assigned 1:1 to treatment with AST-120 or placebo. The primary endpoint was a composite of dialysis initiation, kidney transplantation, or doubling of serum creatinine. The EPPIC trial pooled population was evaluated with the same statistical methods used for analysis of the primary and secondary efficacy endpoints. The trials were registered on ClinicalTrials.gov (NCT00500682 [EPPIC-1] and NCT00501046 [EPPIC-2]). Results: An analysis of the placebo population suggested baseline urinary protein to urinary creatinine ratio (UP/UCr) ≥1.0 and hematuria were independent risk factors for event occurrence and eGFR lowering. Analysis of the high risk patients revealed a difference in the primary endpoint occurrence between treatment groups, if angiotensin-converting enzyme inhibitors and/or angiotensin receptor blockers were administered (hazard ratio 0.74, 95% confidence interval 0.56-0.96). Also, the eGFR changes from baseline in the AST-120 group were smaller than that in the placebo group (P = 0.035). Conclusions: CKD progression may have an association with baseline UP/UCr and hematuria. Treatment with AST-120 may delay the time to the primary endpoint in patients with progressive CKD receiving standard therapy, thus warranting further investigation. Electronic supplementary material. The online version of this article (doi:10.1007/s10157-017-1447-0) contains supplementary material, which is available to authorized users.